SEJARAH POSTMODERN DAN PENGARUH KEPEMIMPINAN KRISTEN YANG PROFESIONAL TERHADAP PERKEMBANGAN ZAMAN - Hery Budi Yosef (CV. Denasya Smart Publisher, 2024)
The large amount of research that examines leadership has made it possible that the lack of quality in a leader has recently stopped using Bible principles as a strong weapon to minimize the values and direction of the times which are now rapidly changing, especially among God's servants in dealing with Christian leadership issues. Listen to many reviews of leadership research which tend to focus on leadership methods (decision models) which are also assessed for the management needs of a company, church or other Christian institution, and so on. Others also discuss the characteristics of a leader, even trying to relate it to the life of Jesus' service as a teacher or leader who also had various backgrounds for foster children (read: His students). Researchers place the leadership pattern of Jesus, who was so strong and authoritative, that his leadership behavior has become an exemplary example for all time until now, even though he had to face increasingly rapidly changing times so that the character's model no longer played a role because it was being swallowed up by rapidly changing times. There are still other discussions about leadership which are answers to leadership issues, in this case touching on the calling of God's servants as leaders in the current era. The main problem lies in leaders who are absorbed in the development of modernism, thus shifting or even eliminating the values of Christ as the center of ideal and strong Christian leadership. The introduction of rationalistic understanding as the beginning of the development of leaders' modernity in leading, rationalist values and mentality enter into leading behavior so that it becomes more humanistic because of a leader's liberalist decisions. That is why researchers emphasize the importance of highlighting the causes of a leader being influenced by rationalism which is the cause of the arrival of modernity or the birth of postmodernity in leadership. So the author wants to find out where the shift is, or at what point a change occurs in the context of leadership. The influence of postmodernism for researchers does not change much of its significance, considering the movements and idealism of Christian leaders in this rapidly changing era. On the contrary, Christian leaders use postmodern influence as a connecting bridge in service programs, and do not shift the value of their 'godliness'. The method used by the author is purely literary and followed by historical references to strengthen the relationship between the birth or emergence of postmodernity from the forces of the rationalist, existentialist and modern eras (contemporary). In relation to Christian leadership, what the author explores is the connection to leadership behavior and the focus on integrity. Highlighting leadership behavior, the author finds ways of thinking, and taking responsibility, and so on in taking and finding the right solution to the problem. In leadership integrity, the author traces his disciplined life (leadership mentality), and his routine spirituality which the author assesses has been inherent in him since receiving a call (read: divine calling) as a leader, either in his church or in the institution he leads.